Speciation and Enrichment of Cadmium and Lead from Water Samples using Fe3O4/rGO Sorbent in Dispersive Magnetic Micro-Solid Phase Extraction with Inductively Coupled Plasma-Optical Emission Spectroscopy - Hanapi, N.S.M.; Safie, W.; Anis, A.L.; Zaini, N.; Ibrahim, W.N.W.; Abdullah, U.A.A.U. (Asian Journal of Chemistry, 2021)
This work reports the development of dispersive magnetic solid-phase extraction (DMSPE) with high resolution ICP-OES for the pre-concentration of cadmium and lead in water samples. The method uses magnetic reduced graphene oxide (Fe3O4/rGO) as adsorbent. The influences of sample pH, extraction time, desorption solvent and desorption time were evaluated and optimized. In the optimized conditions, linear calibration curves for Cd2+ and Pb2+ were obtained in the range of 10-2000 μg L-1 with correlation coefficients of 0.9996 and 0.9995, respectively. Low detection limits of Cd2+ and Pb2+ were found to be 9.03 μg L-1 and 12.4 μg L-1, respectively. Good relative recovery values, in the range of 91-95% and excellent repeatability of 6.4-9.9%, (n = 3) were obtained. The results revealed that Fe3O4/rGO can be a suitable nanocomposite sorbent in the speciation and pre-concentration of Cd2+ and Pb2+ for tap water and drinking water samples. The method is rapid, selective, reliable and environmentally friendly for the determination of Cd2+ and Pb2+ in water samples.